Women and monastic Buddhism in early South Asia rediscovering the invisible believers - Kaushik, Garima (London [u.a.] Routledge, 2016)
This book uses gender as a framework to offer unique insights into the socio-cultural foundations of Buddhism. Moving away from dominant discourses that discuss women as a single monolithic, homogenous category-thus rendering them invisible within the broader religious discourse-this monograph examines their sustained role in the larger context of South Asian Buddhism and reaffirms their agency. It highlights the multiple roles played by women as patrons, practitioners, lay and monastic members, etc. within Buddhism. The volume also investigates the individual experiences of the members, and their equations and relationships at different levels-with the 'Samgha' at large, with their own respective 'Bhiksu' or 'Bhiksuni Sangha', with the laity, and with members of the same gender (both lay and monastic). It rereads, reconfigures and reassesses historical data in order to arrive at a new understanding of Buddhism and the social matrix within which it developed and flourished
Keywords: Buddhist monasticism and religious orders for women -- India -- History; Buddhism -- India -- History; Buddhist women -- India -- History